Baihui (DU20), Shenmen (HT7) and Sanyinjiao (SP6) target the cAMP/CREB/BDNF and PI3K/Akt pathways to reduce central nervous system apoptosis in rats with insomnia. Issue 12 (December 2022) - Cao, Fang; Xu, Yan; Zhang, Min; Li, Xiaohui; Chen, Yizhen; Zhi, Mujun; Li, Yan
Abstract: Insomnia can cause damage to function and other medical and mental illnesses, and it is also a risk factor for increasing medical care costs. Although simple behavior intervention is feasible in primary medical institutions, the lack of corresponding technical training has obviously restricted its use, patients' autonomy dependence is generally poor, and early missions have some difficulties. Relatively speaking, acupuncture in traditional therapy is more likely to be accepted, but the mechanism is still unclear. In this study, a model of insomnia was constructed using chlorophenylalanine (PCPA) in 6-week-old male SD rats. Electroacupuncture was used to stimulate Baihui (DU20), Shenmen (HT7), and Sanyinjiao (SP6), and the behavior, histopathology, cAMP/CREB/BDNF, PI3K/Akt pathways and the expression of sleep-related factors were observed. Our study showed that IL-1β, PGD2, MT, IL-10, IL-6, TNF-α, IFN-γ and CORT in rats could be regulated after electroacupuncture stimulation. The expression of TrkB, PI3K, Akt, P-TrkB, p-Akt, cAMP, CREB, and BDNF can also be up- or downregulated. Apoptosis-related Bax, Bad and Caspase-3, as well as the monoamine neurotransmitters 5-HT, DA, NE and EPI, were also modulated by electroacupuncture. Taken together, these data illustrate the potential of DU20, HT7 and SP6 as a multitargeted therapy for insomnia in rats. The novelty of the study lies in the description of the Traditional Chinese Medicine stimulation methods different from Chinese Herbs: electroacupuncture stimulates acupoints of sleep factors, cAMP/CREB/BDNF, PI3K/Akt pathways and the multipath and multitarget body response regulation mechanism of apoptosis. Abstract : Electroacupuncture; acupoints; rat; insomnia; apoptosis; mechanism.